KEMAMPUAN PEMBELAJARAN BERBASIS TIK PADA GURU SMP DI KOTA PADANG DALAM MENYAMBUT IMPELEMENTASI KURIKULUM 2013 - Khairi, Ashabul; Danil, Muhammad (Jurnal Ipteks Terapan, 2014)
The aim of this Study is to explain the competences of junior high school teacherâs in Padang to TIK based learning implementation policy on 2013 curriculum. 25 teachers who was experienced teaching for VIII grade was chosen using purposive sampling to be research participant. The result describe 87,4% of sample were categories in high competences and 22,6% of sample were categorized in low competences in TIK implementation during teaching their student. FurtherÂ  information also explain, the low ability to implements showed by low score in four main indicators: a) ability to display information systematically, b) attractive and artistic potential, c) student attachment, and d) student weakness potential. As the lowest score indicators, attractive and artistic potential of TIK implementation should becoming a concern forÂ  further research development.Doi: 10.22216/jit.2014.v8i4.9